The Mediating Role of Monitoring and Collaborative Green Supply Chain in the Relationship between Environmental Drivers and Environmental Performance - Chairit Thongrawd; Jatturong Ploenhad; Kristya Jandasang; Anuch Nampinyo (International Journal of Supply Chain Management, 2019)
The prime objective of the current study is to investigate the impact of the environmental drivers (coercive, normative, mimetic pressures and top management support) and environmental performance. In addition to that the current study has examined the mediating role of monitoring and collaborative green supply chain in the relationship between environmental drivers (coercive, normative, mimetic pressures and top management support) and environmental performance. The aim of this study is to examine the contribution of various factors such as, government regulations, competitors, customers, suppliers, society, banks, and top management, which could pressurize firms to adopt particular green supply chain management (GSCM) approach. Therefore, the objective of this paper is to examine the interrelationships between GSCM approaches, performance, and environmental drivers. SEM-PLS is used to achieve the research objective of the current study. The study which is on Indonesian in author knowledge this is among few pioneering studies exploring the interaction of environmental drivers (coercive, normative, mimetic pressures and top management support) and environmental performance. This study will be helpful for policymakers and researchers in examining the link between environmental drivers (coercive, normative, mimetic pressures and top management support) and environmental performance Indonesian settings.